Oxford Handbooks Online 2014
DOI: 10.1093/oxfordhb/9780199793471.013.65
|View full text |Cite
|
Sign up to set email alerts
|

Digital Media and Perceptions of Source Credibility in Political Communication

Abstract: and KeywordsThe rich research heritage on source credibility is fundamentally linked to processes of political communication and the provision of political information. Networked digital technologies, however, have recently complicated the assessment of source credibility by modifying people's ability to determine source expertise and trustworthiness, which are the foundations upon which credibility evaluations have traditionally rested. This chapter explores source credibility in online contexts by examining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Search for the term “source credibility” on Google Scholar returns an excess of 12,000 results (for an overview of recent publications, especially on the subject of Web content credibility, see Wierzbicki, 2018 ). Research in this subject has ranged from investigating impact of source credibility on politics (Flanagin and Metzger, 2017 ) to healthcare (Kareklas et al, 2015 ).…”
Section: Related Workmentioning
confidence: 99%
“…Search for the term “source credibility” on Google Scholar returns an excess of 12,000 results (for an overview of recent publications, especially on the subject of Web content credibility, see Wierzbicki, 2018 ). Research in this subject has ranged from investigating impact of source credibility on politics (Flanagin and Metzger, 2017 ) to healthcare (Kareklas et al, 2015 ).…”
Section: Related Workmentioning
confidence: 99%
“…Data science has been used and suggested for solutions to digital deception. This shows the enduring value of messenger credibility as discussed by Flanagin and Metzger (2014). Reputations can be discredited for an affordable cost, and reporters are human, so mistakes will happen.…”
Section: Metadata Analysis Of Archival Information-time Content Conmentioning
confidence: 96%
“…Gu et al (2017) observed that the cost to discredit a reporter was $50,000. Flanagin and Metzger (2014) noted the role of credibility in presentation, as well as perceptions of honesty and fairness, even when the message remained constant. Ethos applied to the messenger will be further discussed in the archival data subsection of this article.…”
Section: Ethos: Define a Person Or Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, perceiving an opposing political group or 'opinion camp' as inferior to the own is in turn likely to foster the selection of congruent information. Research into the credibility of information sources highlights that information which stems from a distrusted source is more likely to be disregarded and information search hence guided toward more trustworthy ones (Flanagin & Metzger, 2014). Consequently, when exposed to an overtly congruent or incongruent opinion climate, tolerance toward politically incongruent individuals may decrease, which consequently increases selective exposure to congruent information.…”
Section: Rq1mentioning
confidence: 99%